Dinuclear copper(II) complexes with distant metal centers: weaker donor groups increase catecholase activity - Zerón, Paulino; Westphal, Michael; Comba, Peter (European journal of inorganic chemistry, 2017)
Two dinuclear complexes with Cu···Cu distances above 7 Å were characterized by X-ray diffraction, EPR spectroscopy, solution speciation, and cyclic voltammetry. Both complexes display EPR spectra typical of dipole-dipole-coupled dicopper(II) complexes. The two complexes presented herein are part of a series of dinuclear complexes with catecholase activity, and they exhibit the highest catalytic efficiencies of the series. This is associated with the weaker donor character of the ligands.
Gesehen am 26.0.2018
First published: 23 November 2016